Határon átnyúló világörökségi helyszínekhez kapcsolódó kérdések - Pap, Ági (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The foundation of the UNESCO's World Heritage Program was guided by the principle to create an international cooperation that is able to preserve the cultural and natural values of outstanding importance for humankind. Meeting the requirements of the World Heritage Convention 8 Hungarian sites have been inscribed on the List. However, since cultures do not adjust to political borders, several World Heritage Sites span over the borders. Out of the 8 Hungarian World Heritage Sites 2 extends to the territory of the neighbouring countries, which means that they had to be submitted for the List jointly. Due to the particular state of these World Heritage Sites, a particular situation evolves in the operation of the Heritage Sites. Since the countries own the sites jointly, they need to harmonise their activities in favour of the effective maintenance of these heritage sites. The study deals with the above mentioned territories' problems and their possible solutions.